Antimicrobial, Multidrug Resistance Reversal and Biofilm Formation Inhibitory Effect of Origanum majorana Extracts, Essential Oil and Monoterpenes - Tasneem Sultan Abu Ghazal (PLANTS-BASEL, 2022)
Origanum majorana L. is a widely used medicinal plant; its distilled oil and preparations are extensively utilised in the phytotherapy and food industries. The objective of this study is to evaluate the extracts and the essential oil (EO) of Origanum majorana L, and its monoterpenes for antimicrobial, bacterial multidrug resistance reversing, and biofilm formation inhibitory potency. The composition of EO and n-hexane extract was characterized by GC-MS. In the essential oil terpinen-4-ol (24.92%), trans-sabinene hydrate (25.18%), gamma-terpinene (6.48%), cis-sabinene hydrate (5.44%), p-cymene (4.72%), sabinene (4.53%), alpha-terpineol (4.43%), and alpha-terpinene (3.00%) were found as the main constituents while trans-sabinene hydrate (1.43%), and terpinen-4-ol (0.19%) were detected in the n-hexane extract besides a series of hydrocarbons. The antibacterial activity of EO and terpinen-4-ol, alpha-terpinene, and linalool was also assessed against sensitive and drug-resistant S. aureus, and E. coli strains with MIC values of 0.125-0.250% and 30-61 mu M, respectively. In the efflux pump (EP) inhibitory assay, made by the ethidium bromide accumulation method in E. coli ATCC 25922, and AG100 and S. aureus ATCC 25923, and MRSA ATCC 43300 strains, EO exhibited substantial activity, especially in the E. coli ATCC 25922 strain. Among the EO constituents, only sabinene was an EP inhibitor in sensitive Escherichia strain. In the case of S. aureus strains, EO and sabinene hydrate exhibited moderate potency on the drug-resistant phenotype. The antibiofilm effects of the samples were tested by crystal violet staining at sub-MIC concentration. gamma-Terpinene, terpinen-4-ol, sabinene, sabinene hydrate and linalool were found to be effective inhibitors of biofilm formation (inhibition 36-86%) on E. coli ATCC 25922 and S. aureus MRSA ATCC 43300, while EO was ineffective on these strains. In contrast to this, biofilms formed by E. coli AG100 and S. aureus ATCC 25923 were significantly inhibited by the EO; however, it was not affected by any of the monoterpenes. This observation suggests that the antibiofilm effect might be altered by the synergism between the components of the essential oil.